Mental fatigue: Impairment of technical performance in small-sided soccer games - Badin, O. O.; Smith, M. R.; Conte, D.; Coutts, A. J. (International Journal of Sports Physiology and Performance, 2016)
Purpose: To assess the effects of mental fatigue on physical and technical performance in small-sided soccer games.